Predominance of OXA-48 Carbapenemase-Producing Enterobacterales in a Moroccan Hospital - Belouad, El Mehdi; Benaissa, Elmostafa; El Mrimar, Nadia; Bssaibis, Fatna; Maleb, Adil; Elouennass, Mostafa (International Journal of Microbiology, 2023)
Objective. The emergence of carbapenemase-producing Enterobacterales (CPE) is a major concern that is increasingly reported worldwide. Our study aimed at investigating the resistance of CPE isolates in a Moroccan teaching hospital using phenotypic and genotypic methods. Methods. Enterobacterales strains from March to June 2018 were collected from different clinical samples. The Enterobacterales isolates resistant to third-generation cephalosporins (3GC) and/or carbapenems were subjected to the Carba NP test and an immunochromatographic test for phenotypic detection. Detection of extended-spectrum β-lactamases (ESBL) was also performed following standards. Molecular screening of carbapenemases genes (OXA-48, NDM, blaKPC, blaIMP, blaVIM, and blaOXA-24, blaOXA-23, OXA-51, OXA-58) using conventional multiplex PCR assays was also performed on 143 isolates. Results. Enterobacterales represented 52.7% with a proportion of 21.8% of bacteria resistant to 3GC and/or carbapenems. Within 143 isolates MDR to 3GC, K. pneumoniae, E. coli, and E. cloacae represent 53.1%, 40.6%, and 6.3%, respectively. These strains were isolated mainly from urinary samples (74.8%) in patients admitted to emergency and surgical units. 81.1% of strains are producing ESBL and 29% are carbapenemase producers as confirmed by the Carba NP test, immunochromatographic test, and molecular testing. OXA-48 carriers represent 83.3% of these strains, followed by NDM with 16.7%. blaKPC, blaIMP, blaVIM, and blaOXA-24, blaOXA-23, OXA-51, OXA-58 were not detected in any of these bacteria. Conclusions. A high rate of CPE carrying OXA-48 among Enterobacterales resistant to 3GC and/or carbapenems isolates was found. Strict observance of hospital hygiene measures and more rational use of antibiotics are mandatory. Implantation of carbapenemases detection should be encouraged in our hospital settings to estimate the true burden of the CPE.